Advances in the study of aerobic glycolytic effects in resistance to radiotherapy in malignant tumors - Liu, Yuyi; Feng, Zhengfu; Zhang, Pingmei; Chen, Honghao; Zhu, Song; Wang, Xin (PeerJ, 2023)
Aerobic glycolysis is a metabolic mode of tumor cells different from normal cells that plays an important role in tumor proliferation and distant metastasis. Radiotherapy has now become a routine and effective treatment for many malignancies, however, resistance to radiotherapy remains a major challenge in the treatment of malignant tumors. Recent studies have found that the abnormal activity of the aerobic glycolysis process in tumor cells is most likely involved in regulating chemoresistance and radiation therapy resistance in malignant tumors. However, research on the functions and mechanisms of aerobic glycolysis in the molecular mechanisms of resistance to radiotherapy in malignant tumors is still in its early stages. This review collects recent studies on the effects of aerobic glycolysis and radiation therapy resistance in malignant tumors, to further understand the progress in this area. This research may more effectively guide the clinical development of more powerful treatment plans for radiation therapy resistant subtypes of cancer patients, and take an important step to improve the disease control rate of radiation therapy resistant subtypes of cancer patients.
Keywords: Metabolic reprogramming; Aerobic glycolysis; Cancer; Radioresistance